Implementasi Layanan Endorsement pada Laksmi Muslimah Bridal Gown - Mubarokah, Lailatul; Zaman, Komarun; Anisa, Nur Aini (STIE PENA, 2023)
This study aims to determine the implementation of endorsement services on Laksmi Muslimah Bridal Gown. The data studied is the marketing process carried out by Laksmi before the endorsement (2007-2017) and after the endorsement (2018-2023). As well as observing the endorsement process carried out by Laksmi and the implementation carried out by Laksmi's endorsers on social media. The results of this study show some similarities between theory and practice that have been applied by Laksmi. Both in terms of endorser selection, as well as consistency in making endorsements, not only for new endorsers but also for old endorsers. So that it can be found the reason why Laksmi Muslimah Bridal Gown is able to continue to exist after 6 years of doing the first endorsement.